Relaciones antagonicas sobre el crecimiento micellial de Alternaria solani sorauer, por Trichoderma spp. y Verticillium spp. - Andreu Rodriguez, C.M.=700 1 Cupull Santana, R.; Mayea Silverio, S.; Reinoso Medina, M.
(En, Es)
ilus., 4 ref.
Keywords: ALTERNARIA SOLA; TRICHODERMA; VERTICILLIUM; ANTAGONISMO; CUBA